Designing Coconut Biscuit Packaging Using the Kansei Engineering Method - Zahira Ersa Luna; Chintya Dwi Rahmawati; Alfa Giffari Kautsar; Novi Purnama Sari (Agroindustrial Technology Journal, 2025)
Coconut biscuits are one of the snacks favoured by the Indonesian people. The current coconut biscuits packaging has several shortcomings, namely that the opened biscuits cannot be resealed because they do not have a cover, so bacteria easily contaminate the contents of the product, require additional containers to store the product so that it is difficult to store, the packaging material only uses plastic which causes the product to be easily destroyed, and the product is quickly scattered when the packaging is opened. Therefore, this study aims to determine the design concept for coconut biscuit packaging that aligns with consumer priorities. The coconut biscuit packaging design concept was planned using the Kansei Engineering method with the Principal Component Analysis (PCA) supporting method. The Kansei words obtained were 47 words. The results of the packaging concept obtained were one Principal Component (PC) with the most significant standard deviation on PC 1 with a value of 7.5565, so it can be concluded that the optimal packaging concept is ergonomic and complex.